Pengembangan Sediaan Gel Ekstrak Bonggol Pisang Ambon - Husni, Patihul; Prayitno, Adi; Baitariza, Ardian; Christiningtyas Eryani, Mikhania; Januarti, Melinda (JURNAL FARMASI GALENIKA, 2025)
Ambonese banana (Musa paradisiaca var. Sapientum (L.)) has a tuber with several benefits including for wound-healing. The Ambonese banana tuber contains protein, fat, vitamins A and C. In addition, the tannins, flavonoids, and saponins contained in the sap of the Ambonese banana tuber are beneficial in wound healing. The purpose of this study was to obtain the best gel formula containing extract of Ambonese banana tuber based on physical evaluation. The study was conducted by making three different gel formulations (F1, F2, F3) containing 5% Ambonese banana tuber extract. Physical assessment of the gel preparation included organoleptic tests, pH determination, homogeneity, viscosity, and spreadability evaluation. The results showed that the preparation was in the form of a homogeneous gel with a reddish-brown color and a distinctive odor. The pH of the preparation was around 5-8 with a viscosity between 500-3500 cps and a spreadability of 5-8 cm. F2 is the best gel formula based on physical evaluation during four weeks of storage with a composition of 5% HPMC, 15% propylene glycol, 0.2% methylparaben, 5% Ambonese banana tuber extract, and 100% aquadest.